What Drives Customer Loyalty in Digital Banking? Insights From A Systematic Literature Review of Technology Acceptance and Hedonic–Utilitarian Perspectives - Adhelia Budi Pratiwi; Novita Ikasari (Journal of Management Economic and Financial, 2026)
Digital banking has transformed the way financial institutions deliver services and maintain customer relationships in an increasingly competitive digital environment. Although prior studies have extensively examined technology adoption, the formation of customer loyalty in digital banking remains fragmented, particularly when technology acceptance, hedonic–utilitarian motives, and customer satisfaction are considered collectively. This study aims to synthesize existing empirical evidence regarding the factors that drive customer loyalty in digital banking. Using a Systematic Literature Review (SLR) method guided by the PRISMA 2020 framework, this study reviewed peer-reviewed English-language journal articles published between 2016 and 2026 from Scopus, Emerald Insight, ScienceDirect, and SpringerLink. Following the identification, screening, eligibility assessment, and quality evaluation processes using Parsifal, 43 articles were included in the final synthesis. The findings indicate that perceived ease of use and perceived usefulness remain fundamental determinants of digital banking adoption, while utilitarian motives, such as efficiency, convenience, and functional benefits, more consistently influence customer satisfaction and loyalty. Hedonic motives, including enjoyment and engagement, also contribute to loyalty, although their effects vary depending on contextual factors. Customer satisfaction serves as a key mediating mechanism that links technology acceptance and user experience with customer loyalty. This study concludes that digital banking loyalty is a multidimensional construct involving continued usage intention, satisfaction, emotional attachment, and customer advocacy.